2012
DOI: 10.1016/j.ajpath.2012.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Role of SOCS2 in Modulating Heart Damage and Function in a Murine Model of Acute Chagas Disease

Abstract: Infection with Trypanosoma cruzi induces inflammation, which limits parasite proliferation but may result in chagasic heart disease. Suppressor of cytokine signaling 2 (SOCS2) is a regulator of immune responses and may therefore participate in the pathogenesis of T. cruzi infection. SOCS2 is expressed during T. cruzi infection, and its expression is partially reduced in infected 5-lipoxygenase-deficient [knockout (KO)] mice. In SOCS2 KO mice, there was a reduction in both parasitemia and the expression of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…For example, the tryptophan photoproduct 6-formylindolo [3,2-b]carbazole and kynurenine, endogenous AhR ligands, increase only the Th17 population (37,40), while 2,3,7,8-tetrachlorodibenzo-p-dioxin, a high-affinity exogenous AhR ligand, appears to expand only the Treg cell population (preventing experimental autoimmune encephalomyelitis) (42). Additionally, we demonstrated that AhR expression is associated with modulation of the expression of SOCS, a well-known class of molecules contributing to the regulation of cytokine receptor signaling pathways important in the modulation of the immune response against infection (46,52). In this regard, SOCS1 and SOCS3 expression counteracts the actions of IFN-␥ and IL-6 (46,52,77), which play important roles in the pathogenesis of CM.…”
Section: T Cells and Cd4mentioning
confidence: 88%
See 3 more Smart Citations
“…For example, the tryptophan photoproduct 6-formylindolo [3,2-b]carbazole and kynurenine, endogenous AhR ligands, increase only the Th17 population (37,40), while 2,3,7,8-tetrachlorodibenzo-p-dioxin, a high-affinity exogenous AhR ligand, appears to expand only the Treg cell population (preventing experimental autoimmune encephalomyelitis) (42). Additionally, we demonstrated that AhR expression is associated with modulation of the expression of SOCS, a well-known class of molecules contributing to the regulation of cytokine receptor signaling pathways important in the modulation of the immune response against infection (46,52). In this regard, SOCS1 and SOCS3 expression counteracts the actions of IFN-␥ and IL-6 (46,52,77), which play important roles in the pathogenesis of CM.…”
Section: T Cells and Cd4mentioning
confidence: 88%
“…The suppressor of cytokine signaling (SOCS) family plays an important role in immune responses by modulating cytokine signaling pathways, and AhR has been shown to modulate SOCS2 expression in the mouse model of T. gondii infection (46). SOCS2 is also induced during T. cruzi infection (52) and was shown to be modulated as a result of aspirin treatment (53). Therefore, we examined SOCS1, -2, and -3 expression in the brain tissue of infected mice.…”
Section: Ahr Deficiency Results In Increased Parasitemia and Mortalitmentioning
confidence: 99%
See 2 more Smart Citations
“…However, until now, few studies have provided compelling evidence of cardiomyocyte dysfunction during the establishment of heart failure following infection by T. cruzi (de Carvalho et al 1992, Pacioretty et al 1995, Roman-Campos et al 2009b. Recently, new data have provided supporting evidence of how the left ventricular electrical-mechanical dysfunction observed during the initial stages of chagasic cardiomyopathy occurs (Esper et al 2012, RomanCampos et al 2012. However, the cellular mechanisms underlying cardiomyocyte dysfunction during the late stages of Chagas disease remain unknown.…”
mentioning
confidence: 98%